Mapping Maximum Floodwater Footprints from Sustained Flood Traces - Yiling Lin; Xie Hu; Xiekang Wang; Yunxia Zhang (Water Research, 2026)

Ultrathin wide-bandgap niobate for high-performance photodetection and information encryption - Xiaoqiang Feng; Xiaolin Zhang; Ran Liu; Xiaolong Guo; Yuchan Hu; Lizhikun Gong; Yiling Yu; Lei Yin; Yao Wen; Yuchen Cai; Ruiqing Cheng; Jun He (Science Bulletin, 2026)

Millennium-scale dynamics of microbial carbon metabolism genes in coastal soils along a reclamation chronosequence - Min Wang; Yiling Wang; Hanzhu Li; Yuchen Lu; Xinyi Xu; Hang-Wei Hu; Jizheng He; Bin Ma; Xiaofei Lv (CATENA, 2026)

Tissue-specific metabolic remodeling to opposite fatty acid oxidation regulation in golden pompano identified by dual-tissue multi-omics - Yanyu Zhang; Chenhao Hu; Jingchuan Liu; Sirong Jiang; Qian Liu; Xin Zhou; Yiling Liu; Feibiao Song; Jian Luo (Aquaculture, 2026)

Carrots texture alteration via polyphenol interaction from the perspective of cell wall polysaccharide - Yiling Hong; Lei Zhao; Kai Wang; Zhuoyan Hu; Muyan Xiao; Zhenlin Xu; Jianyong Wu; Xuwei Liu (Food Chemistry, 2026)

Phylogenomics of Rhinogobius gobies reveal northern-southern divergence and trait evolution in China - Suhan Liu; Qinwen Xue; Yun Hu; Jiantao Hu; Yiling Pan; Yun Bu; Jiliang Wang; Jianhong Xia 夏建宏; Chenhong Li 李晨虹 (Molecular Phylogenetics and Evolution, 2026)

New record of the eightbarbel loach, Lefua costata (Kessler 1876) in Zhejiang, China, with comments on Lefua sayu (Herre and Lin 1936) - Yangkai Shao; Jiantao Hu; Yiling Pan; Chenhong Li (Ichthyological Research, 2026)

Environmental stress-stable bigels structured by sitosterol–oryzanol and guar gum: Dual-network mechanism and food-relevant applications - Lijuan Han; Yiling Xu; Shiqi Zhang; Mengyuan Xie; Yifeng Han; Hailong Zhang; Chun Hu; Jiangtao Feng (Food Hydrocolloids, 2026)

Characterization of the NFAT Gene Family in Grass Carp (Ctenopharyngodon idellus) and Functional Analysis of NFAT1 During GCRV Infection - Yao Shen; Yitong Zhang; Chen Chen; Shitao Hu; Jia Liu; Yiling Zhang; Tiaoyi Xiao; Baohong Xu; Qiaolin Liu (Fishes, 2025)
Nuclear factors of activated T cells (NFATs) are pivotal regulatory factors of immune responses, primarily by modulating T cell activity and regulating inflammatory cytokine gene transcription. The grass carp reovirus (GCRV) triggers a serious hemorrhagic condition, posing a significant threat to sustainable grass carp (Ctenopharyngodon idella) aquaculture. However, the precise function of NFAT in the host’s defense against GCRV infection is mostly undefined. This study comprehensively identified and characterized the NFAT genetic family in grass carp, cloned grass carp NFAT1 (CiNFAT1), and investigated its expression and function during GCRV infection. Eight NFAT genes encoding seventeen isoforms have been detected within the grass carp’s genomic sequence, distributed across six different chromosomes. Comparative analysis revealed homology with zebrafish NFATs. CiNFAT1 possesses a 2697 bp open reading frame, encoding 898 amino acids, and contains conserved Rel homology domain (RHD) and NFAT-homology (IPT) domains. Quantitative PCR (qPCR) revealed ubiquitous CiNFAT1 expression in healthy grass carp tissues, with the highest expression in gills and skin and the lowest in liver. Following GCRV challenge in vivo, CiNFAT1 expression in immune tissues (liver, spleen, kidney, gill, intestine) showed dynamic changes over time. In vitro experiments in CIK cells demonstrated that CiNFAT1 expression peaked at 12 h post-GCRV infection. Further functional studies revealed that overexpression of CiNFAT1 significantly reduced GCRV replication at 36 h post-infection. This reduction was accompanied by elevated expression of type I interferon (IFN-I) and interferon regulatory factor 7 (IRF7) at 24 and 36 h, respectively, as well as modulated IL-2, IL-8, and IL-10. Conversely, RNA interference-mediated knockdown of CiNFAT1 enhanced GCRV VP5 and VP7 mRNA levels and suppressed IL-2 and IL-8 expression. These results suggest that CiNFAT1 contributes to anti-GCRV immunity by promoting antiviral and inflammatory cytokine responses, thereby inhibiting viral replication. This study provides a foundational understanding of the NFAT genetic family in grass carp and highlights an important role of CiNFAT1 in mediating the body’s inherent defense mechanism against GCRV infection, offering insights for disease control strategies in aquaculture.

Curcumin activates the JAK-STAT signaling pathway to enhance the innate immune response against porcine epidemic diarrhea virus infection in vivo and in vitro - Qiancheng Jiang; Xiangyang Liu; Jianbo Yuan; Shujuan Zhang; Yiling Zhang; Zifei Kan; Zheng Niu; Li Zhang; Xia Hu; Yang Zhou; Jing Wang; Fei Li; et al. (Veterinary Microbiology, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Deep learning MRI-based radiomic models for predicting recurrence in locally advanced nasopharyngeal carcinoma after neoadjuvant chemoradiotherapy: a multi-center study - Chunmiao Hu; Congrui Xu; Jiaxin Chen; Yiling Huang; Qingcheng Meng; Zhian Lin; Xinming Huang; Li Chen (Clinical & Experimental Metastasis, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Effect of psychrotrophic Lactiplantibacillus plantarum L75 with exoploysaccharides-producing property on fermentation, bacterial community, and antioxidant activity of oat silage at low temperature - Rina Su; Xinyuan Cui; Hao Guan; Wencan Ke; Ying Liang; Hu Chen; Neha Sheoran; Mengya Jia; Yiling Yang; Lizhuang Hao; Guojun Zhao; Xusheng Guo (Animal Feed Science and Technology, 2024)

Enhanced removal of phenolic pollutants over MnO2 initiated by peracetic acid: In situ generation of a heterogeneous Mn(III)-hydroperoxo complex - Xueyan Liu; Kangping Cui; Yiling Yao; Xing Chen; Chen-Xuan Li; Yihan Chen; Zhenhu Hu; Minshu Cui (Chemical Engineering Journal, 2024)

System simulation and multi-objective optimization methodology for sustainable municipal solid waste classification management: A case study in China - Jiayue Zhang; Zongguo Wen; Yupeng Hu; Fan Fei; Yihan Wang; Yiling Xie (Sustainable Production and Consumption, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

Non-radical activation of persulfate with Bi2O3/BiO1.3I0.4 for efficient degradation of propranolol under visible light - Yuehua Deng; Qianqian Che; Yani Li; Jiating Luo; Xiang Gao; Yan He; Yiling Liu; Tong Liu; Xiaolong Zhao; Xiaobin Hu; Wei Zhao (Journal of Environmental Sciences, 2024)

SiOC/CNTs composites as anodes for lithium-ion batteries - Changhao Hu; Zhuoqi Cen; Yiling Quan; Qinghua Zhang; Xigao Jian; Kun Liang; Yujie Song; Jian Xu (Chemical Engineering Journal, 2024)

Correction to: Structure-activity relationships and pharmacokinetic evaluation of L-cystine diamides as L-cystine crystallization inhibitors for cystinuria - Longqin Hu; Haifa Albanyan; Jeffrey Yang; Xiangduan Tan; Yiling Wang; Min Yang; Xiaodi Zhong; Michael D. Ward; Amrik Sahota (Medicinal Chemistry Research, 2024)

Structure-activity relationships and pharmacokinetic evaluation of L-cystine diamides as L-cystine crystallization inhibitors for cystinuria - Longqin Hu; Haifa Albanyan; Jeffrey Yang; Xiangduan Tan; Yiling Wang; Min Yang; Xiaodi Zhong; Michael D. Ward; Amrik Sahota (Medicinal Chemistry Research, 2024)
Cystinuria is a rare genetic disorder characterized by defective l -cystine reabsorption from the renal proximal tubule, resulting in abnormally high concentrations of L-cystine and subsequent l -cystine crystallization and stone formation in urine. l -Cystine diamides have shown great promise as inhibitors of l -cystine crystallization. The free α-amino groups in l -cystine diamides have previously been shown to be necessary for l -cystine crystallization inhibitory activity. In this study, three additional series of l -cystine diamide analogs were designed to explore further the structure-activity relationships for l -cystine crystallization inhibition. It has been demonstrated that the middle disulfide bond is required for optimal l -cystine crystallization inhibitory activity, and the only regions that can be modified are the two terminal amides. The presence of another basic amine 2–3 atoms away from the amide nitrogen is also critical for optimal activity. Disulfide exchange was found to be the main metabolic pathway resulting in the formation of two molecules of the active mixed disulfide metabolite from a single l -cystine diamide. l -Cystine diamides have the potential to be developed into a much-needed therapy for cystinuria.

Zinc-associated phospholipid metabolic alterations and their impacts on ALT levels in workers - Yuanyuan Wang; Yiling Li; Qiying Nong; Guohuan Zhang; Nian Liu; Hua Guo; Qinghao He; Lihong Liu; Guangbo Qu; Bin He; Ligang Hu; Guibin Jiang (Science of The Total Environment, 2024)

Microcystis-dominated paddy crusts enhancing the cadmium accumulation in rice plant (Oryza sativa L.) - Xiaolin Kuang; Zhixuan Wang; Liang Peng; Yuanlong Wang; Huijuan Song; Changwu Li; Ke Song; Yiling Hu (International Biodeterioration & Biodegradation, 2024)

Pickering emulsions stabilized by egg white protein-alginate nanoparticles: Freeze-thaw stability after heating - Yiling Zhan; Siyu Qin; Yan Zeng; Qiwei Xu; David Julian McClements; Kun Hu (Food Hydrocolloids, 2024)

Ecological responses and functional significance of paddy crust in the southern Chinese environment - Xiaolin Kuang; Yiyi Hu; Shaoning Chen; Yili Ge; Yiling Hu; Huijuan Song; Ke Song; Liang Peng (Environmental Pollution, 2024)

Ferroptosis participated in inhaled polystyrene nanoplastics-induced liver injury and fibrosis - Yiling Ge; Sheng Yang; Tianyi Zhang; Saisai Gong; Xin Wan; Yuxin Zhu; Yifei Fang; Chengyu Hu; Fei Yang; Lihong Yin; Yuepu Pu; Zaozao Chen; et al. (Science of The Total Environment, 2024)

Application of biological soil crusts for efficient cadmium removal from acidic mine wastewater - Xiaolin Kuang; Yiling Hu; Liang Peng; Dan Li; Huijuan Song; Ke Song; Changwu Li; Yuanlong Wang; Shilong He (Journal of Hazardous Materials, 2024)

Distribution characteristics and migration trends of hexabromocyclododecanes between seawater-sediment system in different seasons of fishing grounds along the Yellow sea and East China sea coasts - Ke Ning; Aifeng Liu; Minggang Zheng; Yiling Li; Shanmin Hu; Ling Wang (Marine Environmental Research, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Identification of lead-binding proteins as carriers and potential molecular targets associated with systolic blood pressure - Qiying Nong; Baowei Chen; Yongshun Huang; Yiling Li; Yuanyuan Wang; Lihong Liu; Bin He; Tiangang Luan; Ligang Hu; Guibin Jiang (Chemosphere, 2023)

Analysis on multi period activity and evolution of Yingxiu-Beichuan fault in Longmenshan area - Ding Xiao; Li Zhongquan; Li Dian; Hu Yiling; Long Wei; Li Jianing; Liu Henglin (Ore and Energy Resource Geology, 2023)

Development of convenient crystallization inhibition assays for structure-activity relationship studies in the discovery of crystallization inhibitors - Jeffrey Yang; Haifa Albanyan; Yiling Wang; Yanhui Yang; Amrik Sahota; Longqin Hu (Medicinal Chemistry Research, 2023)

Global, region and national trends and age-period-cohort effects in colorectal cancer burden from 1990 to 2019, with predictions to 2039 - Shuhua Hu; Yiling Li; Wenmin Zhu; Jialin Liu; Sheng Wei (Environmental Science and Pollution Research, 2023)

Ecological drivers and potential functions of viral communities in flooded arsenic-contaminated paddy soils - Ruichuan Gao; Bin Ma; Min Hu; Liping Fang; Guanhong Chen; Wenqiang Zhang; Yiling Wang; Xinwei Song; Fangbai Li (Science of The Total Environment, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Temperature-sensitive morbidity indicator: consequence from the increased ambulance dispatches associated with heat and cold exposure - Qingchuan Wang; Yiling He; Shakoor Hajat; Jian Cheng; Zhiwei Xu; Wenbiao Hu; Wenjun Ma; Cunrui Huang (International Journal of Biometeorology, 2021)

Reduction of Pb availability during surficial leaching in different types of soils with addition of apatite and oxalic acid - Chenmeng Guo; Weitao Tian; Zhijun Wang; Feiyu Han; Mu Su; Yiling Wu; Zhen Li; Shuijin Hu (Journal of Soils and Sediments, 2019)